Algal remediation of CO2 and nutrient discharges: A review. (15th December 2015) - Judd, Simon; van den Broeke, Leo J.P.; Shurair, Mohamed; Kuti, Yussuf; Znad, Hussein
Abstract: The recent literature pertaining to the application of algal photobioreactors (PBRs) to both carbon dioxide mitigation and nutrient abatement is reviewed and the reported data analysed. The review appraises the influence of key system parameters on performance with reference to (a) the absorption and biological fixation of CO2 from gaseous effluent streams, and (b) the removal of nutrients from wastewaters. Key parameters appraised individually with reference to CO2 removal comprise algal speciation, light intensity, mass transfer, gas and hydraulic residence time, pollutant (CO2 and nutrient) loading, biochemical and chemical stoichiometry (including pH), and temperature. Nutrient removal has been assessed with reference to hydraulic residence time and reactor configuration, along with C:nutrient ratios and other factors affecting carbon fixation, and outcomes compared with those reported for classical biological nutrient removal (BNR). Outcomes of the review indicate there has been a disproportionate increase in algal PBR research outputs over the past 5–8 years, with a significant number of studies based on small, bench-scale systems. The quantitative impacts of light intensity and loading on CO2 uptake are highly dependent on the algal species, and also affected by solution chemical conditions such as temperature and pH. Calculations based on available data for biomass growth rates indicate that a reactor CO2 residence time of around 4 h is required for significant CO2 removal. Nutrient removal data indicate residence times of 2–5 days are required for significant nutrient removal, compared with <12 h for a BNR plant. Moreover, the shallow depth of the simplest PBR configuration (the high rate algal pond, HRAP) means that its footprint is at least two orders of magnitude greater than a classical BNR plant. It is concluded that the combined carbon capture/nutrient removal process relies on optimisation of a number of process parameters acting synergistically, principally microalgal strain, C:N:P load and balance, CO2 and liquid residence time, light intensity and quality, temperature, and reactor configuration. This imposes a significant challenge to the overall process control which has yet to be fully addressed. Graphical abstract: Highlights: Algal PBR research for CO2 fixation & nutrient removal growing at CAGR of 25–30%. Maximum algal growth rates of ∼0.5 g L −1 d −1 equate to a ∼4 h CO2 residence time. Nutrient removals of >90% attainable at hydraulic residence times above 2 days. Process footprint >100 times greater than that of classical biological nutrient removal. Cost benefit dependent on added value of recovered algae.